Komprehensif Penafsiran dan Implementasi Guide to Indonesian Constitutional System Based on UUD 1945 Bagi Generasi Z - Seri Mughni Sulubara; Riska Riska; Yeni Irma Normawati (Universitas Maritim AMNI Semarang, 2024)
The 1945 Constitution as the national constitution is the highest source of law that serves as a benchmark and guideline for other legal regulations. The 1945 Constitution as a written constitution has the highest authority in the Indonesian government system. Amendments to the 1945 Constitution occurred 4 (four) times, where the first change occurred in 1999, 2000, then 2001 and finally 2002. This research uses normative juridical research and library research (literature) which focuses on libraries to obtain data without conducting research in the field. Generation Z tends to be more interested in practical and visual things, so understanding the 1945 Constitution requires a flexible and adaptive strategy by using interactive and multimedia e-learning platforms such as animated videos, infographics, and educational applications to explain the articles of the 1945 Constitution. Integrating the 1945 Constitution in everyday life for generation Z can be done through various approaches that are relevant to their characteristics and needs in several effective ways. So that generation Z is able to understand and integrate the 1945 Constitution into their daily lives, making it a guideline in interacting and contributing to society.